Esterification of the free carboxylic group from the lutidinic acid ligand as a tool to improve the cytotoxicity of Ru(ii) complexes. Issue 2 (12th November 2018) - Honorato, João; Colina-Vegas, Legna; Correa, Rodrigo S.; Guedes, Adriana P. M.; Miyata, Marcelo; Pavan, Fernando R.; Ellena, Javier; Batista, Alzir A.
Abstract : The esterification of the free carboxyl group in ruthenium complexes improves the complex interactions with biomolecules, lipophilicity, and cellular uptake, making them more selective against tumor cells than cisplatin. Abstract : In this study, we report on the selective esterification of the carboxyl group in a coordinated ligand based on the Fischer reaction. The new [Ru(N–O)(bipy)(dppb)]PF6 complex1 was used as a precursor to obtain the ester derivative [Ru(N–Oet)(bipy)(dppb)]PF6 (2 ), and in order to establish the influence of either the free carboxyl group or the ethoxycarbonyl group on biological properties, the [Ru(pic)(bipy)(dppb)]PF6 complex (3 ) was synthesized for comparison (dppb = 1, 4-bis(diphenylphosphino)butane, bipy = 2, 2′-bipyridine, N–O = mono-deprotonated 2, 4-pyridinedicarboxylic acid, N–Oet = 4-ethoxycarbonyl-2-pyridinecarboxylic acid). All three complexes interact weakly with human serum albumin (HSA) with K b values ranging from 10 1 –10 4 M −1, suggesting a spontaneous interaction with this protein by electrostatic (1–2 ) or van der Waals interactions (3 ). Moreover, complex/DNA-binding experiments indicate that complexes2 and3 interact weakly with DNA, while no interaction is observed between complex1 and DNA, probably due to the repulsion involving the free carboxylate group/DNA-phosphate. Anti- Mycobacterium tuberculosis (MTB) activity and cytotoxicity assays against one normal cell line V79 (hamster fibroblast) and three human cancer cell lines A549 (lung), MCF7 and MDA-MB-231 (breast) revealed that complexes2 and3 exhibit good activity against MTB and tumor cells, presenting high cytotoxicity (low IC50 ). On the other hand, complex1 is practically inactive. Therefore, the best biological results found for complex2 can be attributed to its esterification, improving the lipophilicity and cellular uptake, in order to facilitate its passive permeation through the tumor cell membranes allowing for cell death, as well as DNA and HSA interactions, when compared with complex1 .